Penggunaan Bahasa Jawa Oleh Etnik Mandailing Dalam Komunikasi Sehari Hari di Jalan Datuk Kabu, Pasar III Tembung - Pardede, Kiky Yohana; Matondang, Armansyah (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to examine the phenomenon of Javanese language use by the Mandailing ethnic group in everyday communication on Jalan Datuk Kabu, Pasar III, Tembung, Medan. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that the Mandailing community actively uses Javanese in various social contexts, particularly in cross-ethnic interactions in market environments, neighborhoods, and workplaces. The forms of language use include code-mixing, code-switching, and lexical borrowing, with the ngoko variety dominating informal conversations. The primary motivation for using Javanese is to facilitate communication, strengthen social bonds, and adapt to the Javanese-majority environment. However, this phenomenon also limits the use of the Mandailing language, especially among younger generations. The study concludes that while the use of Javanese reflects a positive process of social integration, efforts to preserve the Mandailing language are necessary to maintain the sustainability of local cultural identity.